Psikhologicheskie osobennosti proyavleniya aktivnosti lichnosti yunogo sportsmena v professional'nom samoopredelenii - Bagina, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Detailed analyses of the most pithy researches in the field of youth's career-guidance and professional self-determination are presented in the article. Author highlighted researchers' views at an occupational selection, youth's professional self-determination, professional self-evaluation and in some other fundamental points of the problem. Besides that, the author tried to adopt the most valuable notions of career-guidance theories to the problems of young athletes' occupation choosing. In conclusions of the article, author suggests her own points concerning in the problem of youth's professional self-determination.